IMPACT OF MYOPIC LOSS AVERSION ON INDIAN MIDDLE AGED INVESTORS TRADING BEHAVIOUR - Auxilia, P.A.Mary; G.Y.Vishwanath; P.K.Jayan (International Journal of Psychosocial Rehabilitation, 2020)
This paper studies the influence of frequent information on stocks and its influence on the myopic behavior of investors. Generally investors are risk averse and loss in short term brings a great impact on the minds of investors which makes them myopic to the long term benefits. Investors continuously receiving information on stock performance exhibit myopic loss aversion (MLA) compared to those who do not receive information on their investments frequently. In this research Indian investors myopic behavior is studied to examine whether myopic loss aversion is present in middle aged group and how continuous information on stocks makes them to evince MLA. We observe that middle aged investors are moderate risk takers and they react to the stock information adversely loosing future benefits. Men invest more than women but percentage of women exhibiting MLA is less compared to men as women don’t check stock information frequently like men.